Aplikasi Pembelajaran English Grammar Berbasis Game Android - Bellaniar Ismiati, Maria; Hermawan, Latius; Widiastuti R., Paskalina (Jurusan Teknologi Informasi Universitas Semarang, 2020)
Learning English in class is often carried out in a conventional way such as explaining using a whiteboard, doing practice exercises with pen and paper, and memorizing material from a book / dictionary. Such conventional teaching and learning processes often make students bored and feel the material presented is difficult to understand. One way that can be used to overcome this problem is to create a tool that uses technology, such as games.Gra-Pe Warrior game which has an adventure game concept with penguins as the main character where each level of the player must answer questions about grammar. Gra-Pe Warrior game has become a new learning that further increases motivation in learning. This is evidenced by the results of a descriptive questionnaire test which shows that> 90% of respondents are interested because learning in the form of games is more interesting because it is equipped with several questions about grammar at each door when leveling up.